2011
DOI: 10.1111/j.1460-9592.2011.03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Controversial issues in pediatric regional anesthesia

Abstract: Regional anesthesia in children has reached in the last decades a widespread approval and today is a valid and effective technique used in the daily activity in many pediatric centres. Data from surveys and studies show the very low rate of complications and suggest that the use of regional techniques in children is at least as safe as general anesthesia alone. Despite these evidences there are aspects still creating discussions on the best approach to avoid or prevent risks and on the way to make this techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 53 publications
1
20
0
3
Order By: Relevance
“…[8,9] Pediatric regional Anesthesia Network (PrAN) reported a preliminary evaluation comparing regional anesthesia in awake, sedated, and anesthetized children that indicated no difference in similar transient complication rates. [10,11] Mossetti and Ivani [12] confirmed that pediatric regional anesthesia, when performed following strict guidelines, is at least as safe as general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Pediatric regional Anesthesia Network (PrAN) reported a preliminary evaluation comparing regional anesthesia in awake, sedated, and anesthetized children that indicated no difference in similar transient complication rates. [10,11] Mossetti and Ivani [12] confirmed that pediatric regional anesthesia, when performed following strict guidelines, is at least as safe as general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these techniques hold promise to reduce the total amounts of analgesics needed, also in neonates. 29 Regional anesthesia in children has reached widespread use. Although some techniques are indeed routinely used in clinical care, we would like to make the point that these interventions also have to undergo prospective studies in neonates, also taking into account significant learning curves and team performance as essential for the appropriate conduction of these trials.…”
Section: Locoregional Anesthesia and Minimally Invasive Techniquesmentioning
confidence: 99%
“…29 Ten-fold dosing errors with intravenous paracetamol 46 and propofol infusion syndrome 50 were reported and a case of hyperalgesia 49 following opioid exposure in a newborn has been published. Caregivers should be aware of contemporary management of the above-mentioned complications.…”
Section: Clinical Practice and Research Directions: In Search Of Amentioning
confidence: 99%
“…The incidence in the paediatric population is even lower although due to phy siologic higher intracompartment pressure (13-16mmHg vs. 0-10 mmHg) children are at greater risk of ACS (ref. 9 ). Identified risk factors for ACS are: male gender, young age <35 years, open fracture, intramedullary nailing, anticoagulation therapy, high-energy and penetrating trauma, vascular injuries, tourniquet use, haemophilia and complications of intravenous and intraosseous infusions 8,[10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Intracompartment pressure monitoring (ICP) is considered as a "gold standard" for ACS diagnosis and for decompressive fasciotomy indication 5,14,16,24,27 . The normal intracompartment pressure is in between 0-8 mmHg or below 10-12 mmHg according to different data 9,[28][29][30] . Pain is common with the ICP pressure over 20 mmHg and pressure over 30 mmHg is considered to be indication for emergency fasciotomy 8,10,27,31,32 , but the precise value varies in the literature between 30-45 mmHg [33][34] .…”
Section: Introductionmentioning
confidence: 99%